Catalytic test-method for determination of ruthenium microquantities based on methyl orange oxidation with potassium periodate - E. G. Khomutova; N. A. Maltseva; S. A. Zagorodnikova (Тонкие химические технологии, 2012)
A catalytic test-method for the determination of ruthenium based on methyl orange oxidation by potassium periodate at pH =1 on a paper carrier was proposed. The conditions for the indicator reaction performance were optimized. It is possible to determine ruthenium in the range of its concentrations 0.010 ÷ 0.55 µg/ml .The detection limit equals to 0.0035 µg/ml, the relative standard deviation (RSD) is not higher than 0.058. The accuracy of the analysis results was confirmed by the traditional added - found method.